2019
DOI: 10.1002/hep.30695
|View full text |Cite
|
Sign up to set email alerts
|

The Quality and Outcomes of Care Provided to Patients with Cirrhosis by Advanced Practice Providers

Abstract: Cirrhosis is morbid and increasingly prevalent, yet the U.S. health care system lacks enough physicians and specialists to adequately manage patients with cirrhosis. Although advanced practice providers (APPs) can expand access to cirrhosis‐related care, their impact on the quality of care remains unknown. We sought to determine the effect on care quality and outcomes for patients managed by APPs using a retrospective analysis of a nationally representative American commercial claims database (Optum), which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 34 publications
(80 reference statements)
2
34
0
Order By: Relevance
“…Our data suggested that, more so than visits with APPs without prior subspecialty consultation or subspecialist visits without APP involvement, care quality and outcomes were optimized for patients who saw APPs and subspecialists, including when the APP practiced independently. 20 The key finding from our study was that outcomes were most improved when patients were seen by both APPs and subspecialists.…”
Section: What Is Known About the Role Of Apps In Chronic Liver Disease Care?mentioning
confidence: 66%
See 1 more Smart Citation
“…Our data suggested that, more so than visits with APPs without prior subspecialty consultation or subspecialist visits without APP involvement, care quality and outcomes were optimized for patients who saw APPs and subspecialists, including when the APP practiced independently. 20 The key finding from our study was that outcomes were most improved when patients were seen by both APPs and subspecialists.…”
Section: What Is Known About the Role Of Apps In Chronic Liver Disease Care?mentioning
confidence: 66%
“…23e25 Second, we recently studied the quality and outcomes of care provided by APPs to patients with cirrhosis in the United States. 20 We found that patients who received care from APPs were more likely to be screened for hepatocellular carcinoma and esophageal varices as well as receive evidence-based care for secondary prevention of overt hepatic encephalopathy. Furthermore, APPs were associated with a lower confounder-adjusted risk of both 30-day readmissions and mortality.…”
Section: What Is Known About the Role Of Apps In Chronic Liver Disease Care?mentioning
confidence: 82%
“…As Tapper et al state, “the U.S. health care system lacks enough physicians and specialists to adequately manage patients with cirrhosis.” As the prevalence of cirrhosis continues to rise, comprehensive care of this population that is mindful of their complex medical and psychosocial needs is essential. The authors provide evidence to justify improved quality and clinical outcomes with APP‐based care.…”
Section: What Are the Implications Of The Current Study For Health Camentioning
confidence: 99%
“…(3) In other complex medical conditions, the involvement of advance practice providers (APPs; physician assistants, nurse practitioners) has resulted in benefits across clinical outcomes, patient satisfaction, and quality of life. (4) There are limited data evaluating the impact of APPs on patient outcomes in cirrhosis care.In this issue of Hepatology, Tapper et al (5) present a retrospective analysis of the 2001-2015 Optum Clinformatics database of patients with private insurance. Using the records of 389,257 adult patients with 2 or more cirrhosis claims, the authors performed a detailed statistical analysis to evaluate the effect of APP care on cirrhosis-related outcomes (30-day readmissions, survival) and quality-of-care metrics (hepatocellular carcinoma [HCC] and variceal screening, rifaximin use after discharge for hepatic encephalopathy [HE]).…”
mentioning
confidence: 99%
See 1 more Smart Citation